Forecasting Export Volume of Indonesian and Colombian Coffee in the World Market using ARIMA Model - Zuhdi, Fadhlan; Maulana, Achmad Subchiandi; Rambe, Khoiru Rizqy (Signifikan: Jurnal Ilmu Ekonomi, 2023)
Colombian coffee exports influence Indonesian coffee exports in the short term, so this study aims to forecast the export volume of Indonesian and Colombian coffee in the future. The study used time-series data from 2001 to 2021, further analyzed using the ARIMA model. Based on the projection, Indonesian coffee export is projected to increase with an average value of 1.14 percent and a potential increase of 1.79 percent. However, this result still needed to reach the desired value since the projected coffee export of Indonesia in 2025 only reached 429 172 tons, or lower than the export quantity of Colombian coffee in 2011. This finding indicated that Indonesian coffee export tended to increase stagnantly and was considered low compared to the increasing export of Colombian coffee.JEL Classification: C22, C53, E37, F17, Q13How to Cite:Zuhdi, F., Maulana A. S., & Rambe, K. R. (2023). Forecasting Export Volume of Indonesian and Colombian Coffee in the World Market using ARIMA Model. Signifikan: Jurnal Ilmu Ekonomi, 12(1), 57-68. https://doi.org/10.15408/sjie.v12i1.25456.